Dealing with 4-variables by resolution: An improved MaxSAT algorithm - Chen, Jianer; Xu, Chao; Wang, Jianxin (Theoretical computer science, 2017)
We study techniques for solving the Maximum Satisfiability problem (MaxSAT). Our focus is on variables of degree 4. We identify cases for degree-4 variables and show how the resolution principle and the kernelization techniques can be nicely integrated to achieve more efficient algorithms for the MaxSAT problem. As a result, we present an algorithm of time O⁎(1.3248k) for the MaxSAT problem, improving the previous best upper bound O⁎(1.358k) by Ivan Bliznets and Alexander Golovnev. •A faster algorithm is developed for the important MaxSAT problem.•Two new resolution-based reduction rules are introduced that produce instance structures for efficient branching processes.•The resolution principle and kernelization technique are nicely integrated in handling MaxSAT instances.•The algorithm achieves the most significant improvement over the previous best upper bound, compared to the works since 1999.